Ceratopogonidae from Costa Rica (Diptera). - Macfie, John William Scott (Beiträge zur Entomologie = Contributions to Entomology, 1953)
Nomenklatorische Handlungen costaricae Macfie, 1953 (Atrichopogon), spec. n. didymothecae Macfie, 1953 (Atrichopogon), spec. n. lacajae Macfie, 1953 (Atrichopogon), spec. n. pachycnemus Macfie, 1953 (Atrichopogon), spec. n. utricularius Macfie, 1953 (Atrichopogon), spec. n. philotherma Macfie, 1953 (Dasyhelea), spec. n. pyrsonota Macfie, 1953 (Dasyhelea), spec. n.